2013
DOI: 10.1080/01434632.2013.845199
|View full text |Cite
|
Sign up to set email alerts
|

Hot and cold ethnicities in the Baltic states

Abstract: The article discusses the temperatures of the main ethnic groups in the Baltic states: Estonians, Latvians, Lithuanians, and their three Russian-speaking communities, and the Latgalian and Polish minority groups in Latvia and Lithuania, respectively. The study uses a triangulated methodology that includes a survey questionnaire for quantitative study and an associated protocol for a semi-structured focus group interview. The aim of the methodology is to make the notion of ethnic temperature quantitatively asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…shame, pride, guilt, joy, nostalgia). This component builds on earlier research pointing to the importance of the emotional dimension of ELV and indicating that emotional attachment to group identity positively correlates to the level of ethnocentrism and, moreover, mobilizes members for collective action [ 46 , 50 , 51 p304-308]. In earlier research emotional attachment was measured through a self-reported scale regarding participant’s tendency to value cultural heritage and tradition and was included in the six-factor Web Model of intergroup settings.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…shame, pride, guilt, joy, nostalgia). This component builds on earlier research pointing to the importance of the emotional dimension of ELV and indicating that emotional attachment to group identity positively correlates to the level of ethnocentrism and, moreover, mobilizes members for collective action [ 46 , 50 , 51 p304-308]. In earlier research emotional attachment was measured through a self-reported scale regarding participant’s tendency to value cultural heritage and tradition and was included in the six-factor Web Model of intergroup settings.…”
Section: Methodsmentioning
confidence: 92%
“…Our scale, similar to those used in previous studies, aimed to reflect a broad range of domains of language use, taking into account use of both the minority and dominant language in family circles, immediate social networks, with friends, in schools, institutions, services, public events, and on social media (12 items, α = .93). Previous scales of this kind include those by Allard & Landry [36], Ehala & Zabrodskaja [46] and the EuLaViBar Project [47]. In comparison with previous tools, we addressed frequent patterns of interrupted intergenerational language transmission that often skip the parents' generation, but are based rather on the oldest family members as well as other relatives who transmit the language to the youngest generations.…”
Section: Language Transmissionmentioning
confidence: 99%
“…Izlases apjoms katrā valstī bija apmēram 1000 respondentu: Igaunijā -538 igauņi un 460 krieviski runājošo; Latvijā -419 latviešu, 406 krieviski runājošie un 200 Latgalē dzīvojošo latviešu; Lietuvā -400 lietuviešu, 230 krieviski runājošo un 200 poļu. Šī dzīvotspējas pētījuma rezultāti ir atspoguļoti vairākās publikācijās (Ehala & Zabrodskaja 2011;Ehala & Zabrodskaja 2013;Ehala & Zabrodskaja 2014). Šeit analizētas atbildes uz vairākiem jautājumiem no minētā pētījuma.…”
Section: Metodeunclassified
“…We have conducted 18 in-depth individual interviews with speakers of various ages (ranging from mid-20s to mid-80s) and two focus groups -one at the beginning of the research process (November 2015) and the other 6 months later (April 2016). The interview questions were loosely based on Ehala and Zabrodskaja's vitality questionnaire (Ehala and Zabrodskaja 2014) which needed to be modified as it was not fine-tuned for the hybridity present in Arbanasi community.…”
Section: Methodsmentioning
confidence: 99%